Long-Term Exposure to Nitrogen Dioxide and Ozone and Mortality: Update of the WHO Air Quality Guidelines Systematic Review and Meta-Analysis - Kasdagli, Maria Iosifina (2024)
Objectives: We performed a systematic review and meta-analysis on long-term exposure to nitrogen dioxide (NO2) and ozone (O3) with mortality, to expand evidence that informed 2021 the WHO Air Quality Guidelines and guide the Health Risks of Air Pollution in Europe project.Methods: We included cohorts investigating NO2 and O3 mortality from all-causes, respiratory diseases, chronic obstructive pulmonary disease (COPD), acute lower respiratory infections (ALRI); and NO2 mortality from circulatory, ischemic heart, cerebrovascular diseases and lung cancer. We pooled estimates by random-effects models and investigated heterogeneity. We assessed the certainty of the evidence using the Grading of Recommendations Assessment Development approach and Evaluation (GRADE).Results: We selected 83 studies for NO2 and 26 for O3 for the meta-analysis. NO2 was associated with all outcomes, except for cerebrovascular mortality. O3 was associated with respiratory mortality following annual exposure. There was high heterogeneity, partly explained by region and pollutant levels. Certainty was high for NO2 with COPD and ALRI, and annual O3 with respiratory mortality.Conclusion: An increasing body of evidence, with new results from countrywide areas and the Western Pacific, supports certainty, including new outcomes.